Relationship of Socio-Economic Characteristics with Level of Farmers’ Awareness about Climate Change Effect on Water Resources - Preeti Sharma , Lakhwinder Kaur , Ritu Mittal , Samanpreet Kaur and Sukhjeet Kaur, (Indian Journal of Extension Education, 2018)
The present study was conducted to know the relationship of socio-economic variables with the level ofawareness of farmers. The study was conducted in three villages of Punjab with a sample of 120 famers whichwas drawn randomly from villages Talwandi Khurd, Sandhuan and Ran Singhwala. The results indicated thatmost of the respondents belonged to the middle age group (40.83%), matriculates (23.33%), had joint family(77.5%) and had family size of 2-6 members (68.33%). The data further showed that majority of the farmershad high level of awareness regarding effect of climate change on water resources (71.67%) and effect ofheavy rainfall (57.5%). Results further revealed that awareness regarding reasons of climate change wasassociated with family size (268.0), farm area (563.72) and mass media exposure (201.62) at one percentlevel of significance. The study recommends that there is a need to create awareness among farmers andextension personnel should play important role in educating the farmers about climate change, mitigation andadaptation